2021
DOI: 10.3389/fendo.2021.669302
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic Lockdown on the Incidence of New-Onset Type 1 Diabetes and Ketoacidosis Among Saudi Children

Abstract: BackgroundOverburdened healthcare systems during the coronavirus disease (COVID-19) pandemic led to suboptimal chronic disease management, including that of pediatric type 1 diabetes mellitus (T1DM). The pandemic also caused delayed detection of new-onset diabetes in children; this increased the risk and severity of diabetic ketoacidosis (DKA). We therefore investigated the frequency of new-onset pediatric T1DM and DKA in Saudi Arabia during the COVID-19 pandemic and compared it to the same period in 2019.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 23 publications
6
58
1
1
Order By: Relevance
“…At this time, there is a lack of studies regarding diabetic ketoacidosis among patients with COVID-19 in Saudi Arabia. However, an existing study from Saudi Arabia reported that 83 % were admitted for DKA during the lockdown, which was higher than 2019 (73 %; risk ratio = 1.15), after adjusting for age and sex [ 58 ]. Therefore, ketosis and ketoacidosis should be examined in all hospitalized COVID-19 patients to decline the morbidity and mortality risks [ 53 ].…”
Section: Why Diabetes Is Important?mentioning
confidence: 99%
See 2 more Smart Citations
“…At this time, there is a lack of studies regarding diabetic ketoacidosis among patients with COVID-19 in Saudi Arabia. However, an existing study from Saudi Arabia reported that 83 % were admitted for DKA during the lockdown, which was higher than 2019 (73 %; risk ratio = 1.15), after adjusting for age and sex [ 58 ]. Therefore, ketosis and ketoacidosis should be examined in all hospitalized COVID-19 patients to decline the morbidity and mortality risks [ 53 ].…”
Section: Why Diabetes Is Important?mentioning
confidence: 99%
“…The government of Saudi Arabia had implemented timely measures to decline the virus transmission before COVID-19 being declared as a pandemic [ 58 ]. However, in March 2020, after the WHO announces the COVID-19 outbreak a pandemic, and owing to an increase in infected cases, Saudi Arabia executed further defensive measures, comprising a nationwide lockdown, closing of schools, international and national travel restrictions, postponement of elective procedures and non-essential visits to hospitals to combating COVID-19 [ 58 , 59 ].…”
Section: Why Diabetes Is Important?mentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that pediatric patients of T1D presented a higher HbA1c value during the lockdown. The increase is suspected to be correlated with increased BMI, decreased physical activity, and increased screen time [21]. Al-Agha et al [30] found a decrease in HbA1c.…”
Section: Discussionmentioning
confidence: 98%
“…A total of eleven studies [21][22][23][24][25][26][27][28][29][30][31] with 1357 pre-lockdown and 1325 lockdown total participants, consisting of T1D and T2D patients, reported the mean level of HbA1c and estimated A1c which obtained either from CGM or FGM (Figure 2). A pooled estimate showed that lockdown did not significantly give rise to changes in HbA1c parameter (MD=0.06% [95%CI -0.10 to 0.23], I 2 =77%, random-effects).…”
Section: Primary Outcomes Glycated Hemoglobin A1c (Hba1c)mentioning
confidence: 99%